Investigation on microstructure and tribological performance of zirconium boride reinforced AZ91D magnesium alloy: Effect of processing routes. (February 2023) - Ayyanar, S.; Gnanavelbabu, A.; Rajkumar, K.; Loganathan, P.; Vishal, K.
The present research explored the effects of spatially dispersed ZrB2 particles on mechanical characteristics, surface-modified tribo layer and the dry sliding wear of the AZ91D alloy composite. The objective of this study was to reduce the porosity and improve the tribo performance of the AZ91D/ZrB2 composite by a squeeze casting, and the results were compared with those of a stir-cast composite. The influence of ZrB2 on mechanical properties such as hardness, tensile strength, and wear analysis of composites by the pin-on-disk technique was studied. The squeeze cast composite showed a higher hardness of 115 HV and ultimate tensile strength of 275 MPa than the stir cast composite. Stir-cast composite reduces particle rearrangement due to cluster formation, resulting in higher porosity and lower mechanical strength, reducing tribo performance. The refinement of grain structure and porosity reduction of up to 31.61% improves strength, leading to better tribological properties for the squeeze cast composites. The squeeze cast composite containing 12 wt% of ZrB2 showed a minimum wear of 0.024 mm 3 /m, which is 25.14% less than the stir cast composite. The improved wear resistance resulted from a lubricating boron oxide layer (B2 O3 ), confirmed through Raman spectroscopy. Tribo layer, delamination, and plastic deformation were found to be the primary wear mechanisms for the AZ91D/ZrB2 composite that were active throughout the sliding period.